Synthesis and characterisation of an enantiomerically pure scandium pentadienyl complex and its application in the polymerisation of rac-lactide. Issue 3 (21st December 2021) - Münster, Katharina; Raeder, Jan; Walter, Marc D.
Abstract : An enantiomerically pure constrained geometry scandium complex featuring a pentadienyl moiety was synthesised. The complex efficiently catalyses the polymerisation of rac -lactide to give slightly heterotactic, amorphous poly-(lactide). Abstract : The alkyl-functionalised scandium complex [(pdl*SiMe2 N t Bu)Sc(thf)(CH2 SiMe3 )] (2 ) was synthesised in enantiomerically pure form and characterised by NMR spectroscopy and X-ray diffraction analysis. Complex 2 features a chiral constrained geometry ligand derived from the natural compound (1 R )-(−)-myrtenal, in which the pentadienyl (pdl*) fragment coordinates in η 3 :η 2 -allyl-en fashion to the scandium atom. Compound 2 catalyses the polymerisation of rac -lactide at 30 °C and 50 °C yielding amorphous poly(lactide) with slightly heterotactic enchainment ( P m = 0.36 and 0.37). In agreement with the data obtained from GPC and DSC measurements, a chain-end control mechanism is proposed with fast chain propagation relative to the initiation, which leads to broad molecular weight distributions ( Đ ≈ 1.80) and higher than expected molecular weights. Furthermore, chain transfer processes are observed, but only small amounts of transesterification and racemisation occur. Kinetic studies reveal a second-order dependence in rac -lactide (monomer) concentration and a first-order dependence in the concentration of catalyst 2 .